STATE AND PROBLEMS OF ECONOMIC SECURITY OF ENTERPRISES OF THE REAL SECTOR OF UKRAINE'S ECONOMY - VASYLTSIV, Taras; KUNYTSKA-ILYASH, Marta (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to analyze and generalize the current state and development trends of domestic business entities of the real sector of the national economy of Ukraine in the context of the establishment of prerequisites for their economic security.The article focuses on the relevance of the study of the current state of economic security in the real sector of the national economy of Ukraine. The analysis of production volumes and sales of products by industrial enterprises was carried out. The structure of industrial production in Ukraine is analyzed from the point of view of the economic security of domestic enterprises. The characteristics of the main indicators of the development of industrial enterprises of Ukraine in the context of ensuring their economic security are given. The key indicators of the development of industrial enterprises in the system of functioning of the national economy of Ukraine have been demonstrated. The key indicators of the volume and efficiency of the functioning of enterprises in such branches of the national economy of Ukraine as agriculture, agrarian and construction sectors, transport, warehousing, postal and courier activities, transport and communication are summarized. Conclusions are made in the context of modern trends in the development of domestic enterprises of the real sector of the national economy and their impact on the prerequisites for ensuring the economic security of economic entities.It is proved that the development of industry and the real sector of the economy of Ukraine has a controversial nature with signs of uncertainty in the direction of progress, lack of stable financial support for production, in particular products with high added value, and investment guarantee for innovative and technological modernization. Based on the results of the indicative and structural-temporal analysis, the existential challenges of the development and preservation of financial security of the priority sectors of the economy were determined.The applied value of the research results lies in the identification of problematic aspects of the state and development trends of domestic enterprises of the real sector of the national economy in the context of ensuring their economic security.The scientific novelty of the research results lies in the improvement of the methodology for identifying the conditions for ensuring the economic security of enterprises.
Keywords: business entities; economic security; the real sector of the economy; priority industries; security policy